Woman and Art Theraphy, a Vision on Gender Violence - Marina Ojeda; Ana Serrano (Arteterapia, 2008)
Art Therapy with women’s groups in mistreatment situations opens a wide way to the practise and research in our profession. Our experience with a group of women from Cádiz, promoted by the Deputation of Cádiz shows us by a symbolic way, they are able to find a space for the emotional expression, making changes possible as a way to a personal growth. Derived from other specialists or by their own, women who suffer from gender violence must face up to themselves and their circumstances, which no all of them are prepared to do at the same moment, and must be prepared to dismount and rebuild a whole series of defensive and emotional structures which let us see a low self-concept and the lose of their own identity. When a small light switches on and the first change happens, a deep process of reflexion and interior dialogue begins. Art Therapy has a great potential as an engine and vehicle to a symbolic and significant work that place them face to face to themselves, to their own experiences and emotions, integrating them in a less traumatic and more positive approach. Adapting the therapeutic objectives to the personal rhythms, the group places itself at present time, here and now, reflecting to each one their feelings, emotions, and lacks, and the way to reach the wellness and change in all of them. We can know if the objectives have been really complimented, if the symbolic work made during the sessions is translated to a new guideline of behaviour different from the previous one. We would find out if Art Therapy has gone deeper in them if our clients are able to extract responsible, mature and positioned conclusions from a more active attitude over their own experiences and emotions.